Quality of Life Following Amputation or Limb Preservation in Patients with Lower Extremity Bone Sarcoma - Mason, Gary E.; Aung, Lele; Gall, Sarah; Meyers, Paul A.; Butler, Robert; Krug, Sarah; Kim, Mimi; Healey, John H.; Gorlick, Richard (Frontiers in Oncology, 2013)
Purpose: Although functional differences have been described between patients with lower extremity bone sarcoma with amputation and limb-preservation surgery, differences have not clearly been shown between the two groups related to quality of life. The purpose of the study was to determine if there is a difference in overall quality of life in lower extremity bone sarcoma survivors related to whether they had an amputation or a limb-preservation procedure while identifying psychological differences for further evaluation. The main hypothesis was that sparing a person’s limb, as opposed to amputating it, would result in a better quality of life. Patients and Methods: Eighty-two long-term survivors of lower extremity bone sarcoma were studied to make a comparison of the overall quality of life, pain assessment, and psychological evaluations in limb preservation and amputation patients. Forty-eight patients with limb preservation and thirty-four patients with amputations were enrolled in the study. Validated psychometric measures including the Quality of Life Questionnaire (QLQ), the Minnesota Multiphasic Personality Inventory, and visual analog scales were utilized. Results: The overall quality of life of patients with limb preservation was significantly higher than patients with amputation (p-value < 0.01). Significant differences were noted in the categories of material well-being, job satisfiers, and occupational relations. Conclusion: The overall quality of life of patients with limb-preservation appears to be better than for those patients with amputation based on the QLQ in patients surviving lower extremity bone sarcoma. Further analysis needs to verify the results and focus on the categories that significantly affect the overall quality of life.